Politeness and empathic communication in EL1-EIL speech situations - Conlan, Chris (Curtin University of Technology, Perth, Western Australia, 2007)
This paper focuses on an aspect of English as an International Language (EIL) which to date does not seem to have received the attention it deserves - that is, its status as an increasingly recognisable and distinct variety of English. It suggests that EIL can be categorised in ways analogous to the ways in which other varieties of English are categorised, but that while L1 and nativised varieties of English - such as Australian English, Singaporean English etc. - are identified by utilising traditional linguistic (e.g. syntactic, morphological, and phonological) criteria, EIL - as a consequence of the nature of its speaker base - needs to be classified first and foremost in terms of its functional orientation. The paper argues that the functional orientation which is a hallmark of EIL is marked in uses related to lexical mitigation, clause structure, and discourse organisation; and further, that differences in functional orientation have the potential to result in breakdowns in empathic communication when speakers of EIL interact with speakers for whom English is an L1 variety.